2022
DOI: 10.1101/2022.09.27.509832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of the genus Flavobacterium as a reservoir for fish-pathogenic bacterial species: the case of Flavobacterium collinsii

Abstract: Bacteria of the genus Flavobacterium are recovered from a large variety of environments. Among the described species, Flavobacterium psychrophilum and Flavobacterium columnare are causing considerable losses in fish farms. Alongside these well-known fish-pathogenic species, isolates belonging to the same genus recovered from diseased or apparently healthy wild, feral, and farmed fish have been suspected to be pathogenic. Here, we report the identification and genomic characterization of a F. collinsii isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…reported thereafter [28,31,54,55]. Assigning disease causation and confirming whether a ubiquitous microorganism is an infectious agent or is commensal flora of the host remains a challenge for diagnostic microbiologists, specifically for topical diseases [38,56,57]. Although most salmonids are susceptible to tenacibaculosis [15], it was reported that Pacific salmon species in the Pacific Northwest were resistant to mouth-rot disease caused by T. maritimum [see 8].…”
Section: Resultsmentioning
confidence: 99%
“…reported thereafter [28,31,54,55]. Assigning disease causation and confirming whether a ubiquitous microorganism is an infectious agent or is commensal flora of the host remains a challenge for diagnostic microbiologists, specifically for topical diseases [38,56,57]. Although most salmonids are susceptible to tenacibaculosis [15], it was reported that Pacific salmon species in the Pacific Northwest were resistant to mouth-rot disease caused by T. maritimum [see 8].…”
Section: Resultsmentioning
confidence: 99%
“…At the species level, 17 predominant bacterial species are presented in Figure 4B, constituting approximately 50% of the total plastisphere and each exceeding 1% in average abundance in one sample. Recently confirmed as a pathogenic agent, particularly affecting fish, Flavobacterium tructae with an abundance of 9%, was found to be the most prevalent species among the plastisphere community [27]. Arenimonas maotaiensis , a freshwater bacterium, made the second‐largest contribution to the plastisphere community with an abundance of 6%.…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with previous reports (Akbar et al., 2020, 2021; Callens et al., 2016; Freese & Schink, 2011), Proteobacteria and Bacteroidetes were the dominant bacterial phyla in D. magna guts in the present study. Among these, Flavobacteriaceae was the main component family of Bacteroidetes phyla, which is an opportunistic pathogen that is commonly found in aquatic animals and is capable of causing disease under specific conditions (Lee et al., 2023). Preiswerk et al.…”
Section: Discussionmentioning
confidence: 99%